Resonant leptogenesis in minimal U(1)X extensions of the Standard Model - Arindam Das; Yuta Orikasa (Physics Letters B)
We investigate a general U(1)X scenario where we introduce three generations of Standard Model (SM) singlet Right Handed Neutrinos (RHNs) to generate the light neutrino mass through the seesaw mechanism after the breaking of U(1)X and electroweak symmetries. In addition to that, a general U(1)X scenario involves an SM-singlet scalar field and due to the U(1)X symmetry breaking the mass of a neutral beyond the SM (BSM) gauge boson Z′ is evolved. The RHNs, charged under the U(1)X scenario, can explain the origin of observed baryon asymmetry through the resonant leptogenesis process. Applying observed neutrino oscillation data we study Z′ and BSM scalar-induced processes to reproduce the observed baryon asymmetry. Hence we estimate bounds on the U(1)X gauge coupling (gX) and the mass of the Z′ (MZ′) for different U(1)X charges and benchmark masses of the RHN and SM-singlet scalar. Finally, we compare our results with limits obtained from the existing limits from LEP-II and LHC. We find that depending on the U(1)X charges, the masses of RHNs and SM-singlet scalar resonant leptogenesis could provide a stronger limit on gX for MZ′>5.8 TeV which could be probed by high energy scattering experiment in future.